Studi Eksperimental Aplikasi Metode Pengukuran Kecepatan Aliran Air Tanah - Tina Andriani; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Paper disc velocimeter is used to measure the movement of water flow such as the speed and direction of groundwater flow. This equipment has an important component in determining theresults of the speed and direction of groundwater flow namely paper, ink and foam. Indonesia has various types of paper and ink. Spread of ink on paper is divided into two, namely the spread of convection and diffusion. The availability of a variety of local paper in Pekanbaru, itis necessary to study to obtain the characteristics of the spread of ink on local paper using paper disc velocimeter. The purpose of this study is to test the characteristics of ink spread on local paper variations using velocimater paper discs. The benefits of this research are areference to the characteristics of the paper and ink used in the test equipment. The results obtained in this study are Cu values obtained included in the classification of coarse sand,while K obtained 0.018 included in the classification of coarse sand. The maximum ink distribution on paper is 0.3344 cm with a velocity of 0.00007 cm / min. While the minimum inkspread of 0.3343 cm with a speed of 0 cm / min.Keywords: Paper disc velocimeter, local paper, hidrolic conductivity.